2018
DOI: 10.36678/ijmaes.2018.v04i03.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plyometric training and conventional training on agility performance in tennis players

Abstract: Introduction: Recreational collegiate and professional level tennis players are at risk of musculo skeletal injuries. Plyometric training enhances balance and body control during movement, which promotes improvement in agility. Aim of this study is to find out the effectiveness of plyometric training on improving agility in tennis player. Methodology: This study conducted at Madha medical college and hospital, Chennai.Total 30 subjects were selected from population of tennis players by convenience sampling pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Figure 2B depicts a graphical representation of the outcomes of ROBINS-I evaluations. One of the non-RCTs discovered some concerns due to missing data, owing to an approximate 15% dropout rate ( Fernandez-Fernandez et al, 2016 ), two studies had moderate risk of bias in domain of deviations from intended intervention ( Ölçücü, 2013 ; Lakshmikanth et al, 2018 ), and three studies had moderate risk regarding bias in the selection of the reported results ( Ölçücü et al, 2013 ; Fernandez-Fernandez et al, 2018 ; Hotwani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2B depicts a graphical representation of the outcomes of ROBINS-I evaluations. One of the non-RCTs discovered some concerns due to missing data, owing to an approximate 15% dropout rate ( Fernandez-Fernandez et al, 2016 ), two studies had moderate risk of bias in domain of deviations from intended intervention ( Ölçücü, 2013 ; Lakshmikanth et al, 2018 ), and three studies had moderate risk regarding bias in the selection of the reported results ( Ölçücü et al, 2013 ; Fernandez-Fernandez et al, 2018 ; Hotwani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The twelve included papers were carried out between 2008 and 2021, with 443 tennis players. Across the studies, 1) Gender: nine studies focused on men ( Salonikidis and Zafeiridis, 2008 ; Behringer et al, 2013 ; Fernandez-Fernandez et al, 2015 ; Fernandez-Fernandez et al, 2016 ; Fernandez-Fernandez et al, 2018 ; Mohanta et al, 2019 ), no studies focused on female tennis players alone, two studies reported mixed gender ( Lakshmikanth et al, 2018 ; Hotwani et al, 2021 ), and one study did not specify gender ( Gelen et al, 2012 ); 2) Age: all studies recorded the participants’ ages, and an overview of age reports from twelve research revealed that the participants’ ages ranged from 12.5 to 25 years; 3) Tennis experience: eight studies reported on the training experience of the tennis players ( Salonikidis and Zafeiridis, 2008 ; Gelen et al, 2012 ; Behringer et al, 2013 ; Fernandez-Fernandez et al, 2015 ; Fernandez-Fernandez et al, 2016 ; Fernandez-Fernandez et al2018 ; Mohanta et al, 2019 ), ranging from 12 to 96 months, four studies did not report on training experience ( Ölçücü et al, 2013 ; Rathore, 2016 ; Lakshmikanth et al, 2018 ; Hotwani et al, 2021 ); 4) Intervention: regarding the training regimen in this review, four studies conducted PT for the upper and lower extremities ( Behringer et al, 2013 ; Fernandez-Fernandez et al, 2016 ; Mohanta et al, 2019 ; Ziagkas et al, 2019 ), and one study used only upper limb PT ( Gelen et al, 2012 ), six studies used lower-extremity PT ( Salonikidis and Zafeiridis, 2008 ; Fernandez-Fernandez et al, 2015 ; Rathore, 2016 ; Fernandez-Fernandez et al, 2018 ; Lakshmikanth et al, 2018 ; Hotwani et al, 2021 ), but three studies did not detailed description the training protocol ( Ölçücü, 2013 ; Rathore, 2016 ; Ziagkas et al, 2019 ). In addition, three studies combined PT with other types of exercise training (i.e., sprint training, acceleration/deceleration/change of direction drills) ( Fernandez-Fernandez et al, 2015 ; Fernandez-Fernandez et al, 2018 ; Hotwani et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plyometric training has been shown to have a significant positive impact on tennis serve performance in adolescent players. Studies have demonstrated that incorporating plyometric exercises into training routines can lead to improvements in various physical qualities essential for tennis, such as agility, speed, and power(Fernandez-Fernandez et al, 2016;Gelen et al, 2012;Lakshmikanth et al, 2018) Specifically, and research has highlighted that plyometric training, when combined with regular tennis training, results in enhanced physical qualities crucial for tennis players, including serve velocity, agility, and overall performance movements. The findings suggest that integrating plyometric exercises into the training regimen of adolescent tennis players can lead to notable improvements in serve performance, contributing to their overall athletic development and competitive edge on the court.…”
mentioning
confidence: 99%